Hybrid Reinforced Concrete Cross-Section Using Fiber-Reinforced Polymer and Steel Bars - Zahid Hussain; Federico Tuozzo; Gennaro Magliulo; Antonio Nanni (International Journal of Concrete Structures and Materials)
Abstract Fiber-reinforced polymer (FRP) bars offer a promising alternative to conventional steel reinforcement in reinforced concrete (RC) structures, primarily due to their corrosion resistance. However, their intrinsic linear elastic behavior may limit their applications to non-seismic zones or regions with limited seismic activity. To extend their applications in seismic zones such as Seismic Design Category D, a novel approach involving a hybrid-RC (HRC) cross-section is proposed. This approach entails placing FRP bars on the cross-section exterior for corrosion resistance, while steel bars on the inner side of the cross-section to ensure ductility and energy dissipation. This paper presents a methodology for designing HRC cross-sections and evaluates their ductility and energy dissipation capabilities. The discussion encompasses various design aspects of an HRC section including strength reduction factor, minimum reinforcement ratio, reinforcement strain, concrete shear strength, and the impact of confinement on ductility and energy dissipation. Additionally, an illustrative example of a HRC section demonstrates the practicality of the proposed design methodology in practical applications.